Empty Sella Is a Sign of Symptomatic Lateral Sinus Stenosis and Not Intracranial Hypertension - Zetchi, A.; Labeyrie, M.-A.; Nicolini, E.; Fantoni, M.; Eliezer, M.; Houdart, E. (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: Empty sella has been reported in patients with idiopathic intracranial hypertension and is thought to be a sign of elevation of intracranial pressure. However, it can also be found in patients with lateral sinus stenosis presenting with isolated pulsatile tinnitus without signs of intracranial hypertension. We hypothesized that the volume of the sella turcica would be similar in both groups of patients undergoing stent placement for lateral sinus stenosis.MATERIALS AND METHODS: Consecutive patients with idiopathic intracranial hypertension or isolated venous pulsatile tinnitus and undergoing lateral sinus stent placement from January 2012 to December 2017 were included. The primary outcome was the estimated volume of the sella turcica based on preoperative CTA measurements. The ratio of the pituitary gland height/sellar height was calculated on preoperative MR imaging. Sellar volumes were compared among the 3 groups: pulsatile tinnitus, idiopathic intracranial hypertension, and a control group, matched by age and sex.RESULTS: Eighty-eight patients underwent lateral sinus stent placement. The median age was 37 years, and 94% were women. No difference in age, sex, or body mass index was found among the groups. Patients undergoing venous stent placement had significantly higher sellar volumes than the control group (P < 0.001). There was no difference in the sellar volumes (P = .63) or gland/sellar height ratios (P = .25) between the pulsatile tinnitus and idiopathic intracranial hypertension groups.CONCLUSIONS: Empty sella is found in 2 differing groups of patients undergoing lateral sinus stent placement, suggesting that it is a radiologic sign of symptomatic hemodynamic lateral sinus stenosis rather than elevated intracranial pressure.BMIbody mass indexGH/SHratio of pituitary gland height/sellar heightIIHidiopathic intracranial hypertensionIPTisolated venous pulsatile tinnitus